Pharmacokinetics and Pharmacodynamics of Remimazolam (CNS 7056) after Continuous Infusion in Healthy Male Volunteers Part II. Pharmacodynamics of Electroencephalogram Effects - Eisenried, Andreas; Schüttler, Jürgen; Lerch, Marco; Ihmsen, Harald; Jeleazcov, Christian (Anesthesiology, 2020)
Background:Remimazolam (CNS 7056) is a new ultra-short acting benzodiazepine for IV sedation. This study aimed to investigate the electroencephalogram (EEG) pharmacodynamics of remimazolam infusion.Methods:Twenty healthy male volunteers received remimazolam as continuous IV infusion of 5 mg/min for 5 min, 3 mg/min for the next 15 min, and 1 mg/min for further 15 min. Continuous EEG monitoring was performed by a neurophysiologic system with electrodes placed at F3, F4, C3, C4, O1, O2, Cz, and Fp1 (10/20 system) and using the Narcotrend Index. Sedation was assessed clinically by using the Modified Observer's Assessment of Alertness and Sedation scale. Pharmacodynamic models were developed for selected EEG variables and Narcotrend Index.Results:EEG changes during remimazolam infusion were characterized by an initial increase in beta frequency band and a late increase in delta frequency band. The EEG beta ratio showed a prediction probability of Modified Observer's Assessment of Alertness and Sedation score of 0.79, and could be modeled successfully using a standard sigmoid E-max model. Narcotrend Index showed a prediction probability of Modified Observer's Assessment of Alertness and Sedation score of 0.74. The time course of Narcotrend Index was described by an extended sigmoid E-max model with two sigmoid terms and different plasma-effect equilibration times.Conclusions:Beta ratio was identified as a suitable EEG variable for monitoring remimazolam sedation. Narcotrend Index appeared less suitable than the beta ratio for monitoring the sedative effect if remimazolam is administered alone.